Paxillin: A Hub for Mechano-Transduction from the β3 Integrin-Talin-Kindlin Axis - Ripamonti, Marta; Wehrle-Haller, Bernhard; de Curtis, Ivan (Frontiers in Cell and Developmental Biology, 2022)
Focal adhesions are specialized integrin-dependent adhesion complexes, which ensure cell anchoring to the extracellular matrix. Focal adhesions also function as mechano-signaling platforms by perceiving and integrating diverse physical and (bio)chemical cues of their microenvironment, and by transducing them into intracellular signaling for the control of cell behavior. The fundamental biological mechanism of creating intracellular signaling in response to changes in tensional forces appears to be tightly linked to paxillin recruitment and binding to focal adhesions. Interestingly, the tension-dependent nature of the paxillin binding to adhesions, combined with its scaffolding function, suggests a major role of this protein in integrating multiple signals from the microenvironment, and accordingly activating diverse molecular responses. This review offers an overview of the molecular bases of the mechano-sensitivity and mechano-signaling capacity of core focal adhesion proteins, and highlights the role of paxillin as a key component of the mechano-transducing machinery.